A PORTRAIT OF DEVASTATION: SCHOOLING OF YOUNG PEOPLE AND ADULTS IN THE CONTEXT OF BRAZILIAN SOCIETY FROM 2015 TO 2022 - Bellei Oliveira, Rodrigo (2025)
This article analyzes the socio-economic and ideological-political context that marked the schooling processes in Youth and Adult Education (EJA) in Brazilian society between 2015 and 2022. It seeks to answer the following question: what are the relationships established between the schooling processes of young people and adults and the contradictions and challenges generated by the impacts of the capitalist crisis on Brazilian education and society? It analyzes the schooling of young people and adults considering that the capitalist crisis provided advances in conservatism in Brazilian society and education. The official data presented show the significant dismantling of the modality in question and the setback in guaranteeing the right to education for young people and adults. The increase in social and, above all, educational inequalities marked the period studied. Based on this analysis, it reinforces the need to face this adverse context in order to establish EJA as a modality that meets the interests, trajectories and projects of human emancipation and social transformation.